A Latin Renaissance in Reformation Scotland? Print Trends in Scottish Latin Literature, c. 1480–1700. (April 2016) - Reid, Steven J.
Abstract : The full extent of the large body of Latin literature produced by Scots in the early modern period has long eluded scholars. However, thanks to a growing range of research in this field, and particularly to the appearance of several major new bibliographic and electronic resources, it is possible for the first time to map out one aspect of its broad contours. This article uses a database comprising all currently known published first editions of Latin texts by Scots between 1480 and 1700 to examine the extent of Scottish Latin culture in print in the early modern period; how this related to the rise of printed texts in Scots and English; and the major genre types in which Scottish Latin authors published. The database reveals several major trends: firstly, that the publication of Scottish Latin texts reached its zenith in the reign of James VI and I, bolstered by the arrival of a domestic print market but also in part by an increased focus on literacy and education after the reformation; secondly, that by far the largest genres of printed Scottish Latin were poetry and academic theses, and not religious or political texts as might perhaps be expected; and thirdly, that the use of Latin as a literary and academic language in Scotland declined rapidly and irrevocably in the second quarter of the seventeenth century. The article concludes that the production of Latin literature by Scots was unique as an aspect of renaissance culture in Scotland because it had no strongly-defined presence before the reformation of 1560 and only became fully manifest in King James's later reign. It offers potential reasons as to why this may have been the case, and examines some implications the data has for understanding Scotland's developing intellectual and linguistic relationship with England after the union of the crowns. However, the article acknowledges the limited picture provided by print evidence alone and ends by calling for further research to assess how far this trend applies to all Latin literature produced by Scots, particularly the surviving corpus of Latin manuscripts.